TINGKAT KETERAMPILAN DASAR SEPAKTAKRAW PESERTA EKSTRAKURIKULER DI SMAN 6 MANDAU KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS - Fany Alfinda; Ni Putu Nita Wijayanti; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrak: This study generally aims to determine the level of basic skills of extracurricular sepaktakraw participants at SMAN 6 Mandau, Bathin Solapan District, Bengkalis Regency in 2021. The population in this study were all students who took part in the sepaktakraw extracurricular activities at SMAN 6 Mandau in 2021 which consisted of 12 students of class XII IPA and Social Sciences.This study uses a total sampling technique. The instrument in this study was to use the sepaktakraw playing skill test instrument from M. Husni Thamrin, (2006: 6). The results showed that 1 student (8.3%) was in the "very high" category, 2 students (16.7%) were in the "high" category, 5 students (41.7%) were in the "medium" category, 3 students (33.3%) are in the “low” category, and no students (0%) are in the “'very low” category.Key Words: Skills, Sepaktakraw